Size Matters - "Over"investments in a Relational Contracting Setting - Florian Englmaier; Matthias Fahn (Center for Economic Studies and ifo Institute (CESifo), 2015)
The corporate finance literature documents that managers tend to overinvest into physical assets. A number of theoretical contributions have aimed to explain this stylized fact, most of them focussing on a fundamental agency problem between shareholders and managers. The present paper shows that overinvestments are not necessarily the (negative) consequence of agency problems between shareholders and managers, but instead might be a second-best optimal response if the scope of court-enforceable contracts is limited. In such an environment a firm has to rely on relational contracts in order to manage the agency relationship with its workforce. The paper shows that investments into physical productive assets enhance the enforceability of relational contracts and hence investments optimally are too high.
Keywords: C73; D21; D86; G32; 330; relational contracts; corporate finance; capital investments